Risk stratification of cardiovascular complications using CHA2DS2-VASc and CHADS2 scores in chronic atherosclerotic cardiovascular disease. (15th August 2021) - Sen, Jonathan; Tonkin, Andrew; Varigos, John; Fonguh, Sylvanus; Berkowitz, Scott D.; Yusuf, Salim; Verhamme, Peter; Vanassche, Thomas; Anand, Sonia S.; Fox, Keith A.A.; Eikelboom, John W.; Amerena, John; et al.
Abstract: Background The COMPASS (Cardiovascular Outcomes for People Using Anticoagulation Strategies) trial showed that rivaroxaban plus aspirin reduced major adverse cardiovascular events (MACE) in patients with chronic coronary artery disease (CAD) and/or peripheral artery disease (PAD). We explored whether CHA2 DS2 -VASc or CHADS2 scores, well-validated tools for assessing risk of thromboembolic events in atrial fibrillation, can identify vascular patients at highest risk of recurrent events who may derive greatest benefits of treatment. Methods Predictive accuracies of the CHA2 DS2 -VASc and CHADS2 scores for MACE, were assessed in this analysis of the COMPASS trial. Kaplan-Meier estimates of cumulative risk were used to compare the effects of rivaroxaban plus aspirin ( n = 9152) with aspirin alone ( n = 9126) according to risk scores. Results High CHA2 DS2 -VASc (6–9) or CHADS2 (3–6) scores were associated with over three times greater absolute risk of MACE compared with CHA2 DS2 -VASc score of 1–2 or CHADS2 score of 0. The effects of rivaroxaban plus aspirin compared with aspirin alone were consistent across CHA2 DS2 -VASc and CHADS2 score categories for MACE, bleeding and net clinical benefit, with greatest reduction in MACE observed in patients treated for 30 months with highest CHADS2 score (3–6) (hazard ratio = 0.67, 95% CI: 0.53–0.86, p = 0.0012, 25 events per 1000 patients prevented). Conclusion The CHA2 DS2 -VASc and CHADS2 scores can be used in patients with chronic CAD and/or PAD to identify patients who are at highest risk of MACE. Those identified at highest risk by CHADS2 scores had greatest benefit from dual pathway inhibition with rivaroxaban plus aspirin. Clinical Trial Registration: NCT01776424 Highlights: High CHA2 DS2 -VASc/CHADS2 scores were associated with higher risk of MACE in ASCVD. Patients with higher CHADS2 scores had greater benefit of rivaroxaban and aspirin. The net clinical benefit of rivaroxaban and aspirin vs aspirin alone progressively increased as the CHA2 DS2 -VASc score increased - the higher the CHA2 DS2 -VASc score the greater the net clinical benefit.